Effect of mechanical work and selected plant proteases in the production of buffalo meat patties - Ismail, Mohamad Afifi (2021)
Buffalo meat has been used widely in meat processing due to its good binding properties with high protein and low-fat content. However, the major problem rise in the industry is associate with the toughness of the buffalo meat. Therefore, several attempts had been done to improve the palatability of the tough meat by using physical and enzymatic treatment. The lack of studies that explain the relationship of mechanical process and plant protease incorporation on the physicochemical and sensory of buffalo meat patties has led to this study. The objectives of the present work were (ⅰ) to evaluate the physicochemical, sensorial properties and microstructural of buffalo meat patties produced using different mixing equipment (bowl cutter, universal mixer, and meat mixer), (ⅱ) to determine the protease activities in selected plant extracts (ambarella, candlenut, carambola, ginger, jujube, kiwifruit and lemon) and their marination effects on the buffalo meats, and (ⅲ) to evaluate the effects of mechanical work of mixing using the universal mixer and selected plant proteases (kiwifruit and candlenut) on the physicochemical, sensorial and microstructural properties of buffalo meat patties. In the first objective, the textural and sensorial properties of patties produced using the universal mixer were in between the patties produced using the bowl cutter and meat mixer. Besides that, scanning electron microscopy revealed slightly less homogeneity with a large number of pores, and less disruption of patties using the universal mixer. Therefore, the universal mixer was selected to be used for the third objective based on the results obtained. In the second objective, candlenut possessed the highest protease activities at 8.19 U/mL while kiwifruit and ginger showed similar protease activity in the range between 1.41 to 1.67 U/mL. The treatment using plant extract had decreased the water holding capacity of buffalo meat except for ginger. All treatments had increased the Trichloroacetic acid (TCA) soluble peptides content except carambola. Candlenut and jujube treatment had increased the total soluble protein by 38.08% and 32.11%, and salt soluble protein by 7.16% and 8.07%, meanwhile kiwifruit treated meats had the highest collagen solubility at 31.74%. A significant improvement in Warner-Bratzler shear force value was observed in kiwifruit, candlenut and lemon treated samples by 59.74%, 28.07% and 18.95%, respectively. Overall, kiwifruit showed a higher tenderizing effect while candlenut possessed higher protease activity; therefore, both kiwifruit and candlenut were selected to be used for the third objective. In the third objective, marinating buffalo meat with kiwifruit and candlenut extract resulted in increases in the gel strength by 56.81% and 48.13%, and a significant improvement in binding properties. Meanwhile, the addition of kiwifruit and candlenut extract had increased cooking loss by 22.43% and 24.32%, as well as a higher total soluble protein at 79.09 mg/g and 79.40 mg/g raw meat, respectively. The buffalo meat patties added with kiwifruit extract had the lowest hardness value at 46.64, gumminess value at 32.27 and chewiness value at 27.60. The addition of kiwifruit also produced the highest score for tenderness at 7.56. Treatment of protease regardless by addition or marination had disintegrated the protein structure which was revealed by scanning electron microscopy. Overall, using the universal mixer was found to be the most effective in providing a good binding effect, improved sensorial properties and less disruption in microstructural of buffalo meat patties. In enzymatic treatment, kiwifruit and candlenut gave a high tenderizing effect and higher protease activity, respectively. Lastly, the application of the universal mixer together with kiwifruit and candlenut plant protease have led to an improved microstructural, physicochemical properties and palatability of buffalo meat patties. Hence, the present study shows that the application of protease combined with mechanical work of mixing can be a new potential method in producing meat products such as patties.